Investigating EFL Students' Self-Efficacy in Teaching Practicum - Febrian, Maria Lala; Siboro, Efrika; Upa, Yunika; Hertanto, Mustika Aji (PROJECT (Professional Journal of English Education), 2025)
This research is designed to explore students' self-efficacy level during teaching practicum as well as the factors that affect the ratings. The researchers implemented mix method by combining quantitative and qualitative to address the inquiry. The participants consisted 33 EFL students from one of private universities in west Kalimantan. The results demonstrate that EFL students' self-efficacy level during teaching practicum is in the moderately high to very high category. It is indicated by the results of the questionnaire, which shows that the strength dimension has the highest score of 3.60 (very high), the generality dimension with a score of 3.40 (slightly high), and the magnitude dimension with a score of 3.0 (slightly high). Additionally, the elements influencing students' self-efficacy include mastery experience, vicarious experience, verbal persuasion, and psychological arousal.